A quasi-experimental study on teaching discourse markers oh and well = Nghiên cứu bán nghiệm về việc giảng dạy 2 dấu hiệu diễn ngôn oh và well - Trần, Mỹ Dung (2020)
This study focuses on eight selected students in an English center, who will go to America to study as undergraduates in August 2012. They joined a five-week speaking course in which oh and well were taught. They were then compared with other eight students of the same level, who experienced no lesson about oh and well. Moreover, this study only focused on two discourse markers oh and well. These two discourse markers were chosen because they are two of the most frequently used discourse markers in the Inside Out Intermediate, the core material of the course